All Days 2004
DOI: 10.4043/16583-ms
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Spar Responses: Model Tests vs. Analysis

Abstract: The DeepStar Program has sponsored a series of tasks to evaluate the current industry capability in predicting the responses of deepwater theme structures (FPSO, TLP and SPAR). In its Phase IV program, model tests of the FPSO, TLP and SPAR were conducted, and in the Phase V program, engineering companies as well as test basins were invited to evaluate the correlations between the tests and analyses. This paper presents an overview of DeepStar's effort with emphasis on Spar responses. It cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In addition, an experiment using a 1:87 scaled model of a classic petroleum spar platform was conducted to confirm the predicted results. The study showed similar and excellent agreement between predictions and test measurements [23].…”
Section: Introductionsupporting
confidence: 65%
“…In addition, an experiment using a 1:87 scaled model of a classic petroleum spar platform was conducted to confirm the predicted results. The study showed similar and excellent agreement between predictions and test measurements [23].…”
Section: Introductionsupporting
confidence: 65%
“…Evaluation of vortex induced motion (VIM) in offshore floating structures has been largely been carried out for spars. Classic spar, truss spar and cell spar hulls are all known to exhibit VIV (VIM) [1], [2], [6], [7], [8], [9], [10], [12], [13], [14], [15], [16], [19], [27], [28], [29]. [31], [32],…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between main mooring parameters and the truncation factor were put forward, static characteristics of truncated SPAR mooring systems were unchanged. Coupled analysis to the whole system in the time domain were also conducted, attempting to let the global response and mooring tensions of truncation results be consistent with full depth and MARIN test results from Steen et al (2004). After detailed comparison, results of the two truncation system were found correct, and the truncation design was proved to be reasonable and reliable.…”
Section: Introductionmentioning
confidence: 95%
“…Research on a SPAR mooring system working in 913 m water depth was conducted by Wichers and Devlin (2004) and Steen et al (2004). Further truncation design of the same SPAR was carried out in this paper with the water depth reduced to 736 m and 552 m respectively.…”
Section: Introductionmentioning
confidence: 99%